Cucumber Economic Values and Its Cultivation and Breeding - Wang, Haiping (IntechOpen, 2021)
Cucumber is a well-known and popular vegetable because of its rich nutrient profile and versatile uses in culinary, therapeutic and cosmetic purposes. This book provides information on the plant's origins, biology, and breeding as well as research on its economic value, utilization, cultivation, and therapeutic benefits.